Elders health empowerment scale: Turkish translation and psychometric testing - Karabulutlu, Elanur Yilmaz; Turan, Gulcan Bahcecioglu; Oruc, Fatma Gunduz (Wiley, 2021)
Purpose The aim of this study is to adapt Elders Health Empowerment Scale (EHES) to Turkish and to find out the validity and reliability of the scale. Desing and Methods This methodological study was conducted with 300 patients who agreed to participate in the study in Turkey. Findings It was found that Cronbach's alpha reliability coefficient of the scale was .90, item factor loads of the scale ranged between 0.30 and 0.89 and item-total correlation coefficients ranged between 0.30 and 0.84. The one-factor structure of the scale was supported as a result of the CFA and EFA conducted. Good fit index values were obtained as a result of CFA. Practice Implications EHES is a valid and reliable measurement tool for the evaluation of the empowerment states of elders in Turkish society.
Keywords: Elders Health Empowerment Scale; psychometrich testing; Turkish translation